(untitled) (Macedón Tudományos és Kulturális Közlemények, 2020)
Absztrakt A macedón folklór kutatója macedón archaikus énekeket ültetett át macedón nyelvről magyar nyelvre. Abstract The researcher of the Macedonian folklore transferred texts of archaic folk songs from the Macedonian to the Hungarian language.